The Profile of COVID-19 in Patients with Autoimmune Disease: A Case Series - Zubairi Djoerban; Muhammad Alkaff; Dimas Priantono; Dyah Agustina Waluyo; Jessica Marsigit; Chairina Azyka Noor; Oemar Ichsan; Kevin Yonathan; Matdoan Rifkiah Aisyah; Andy William; Uva Rahmah; Wahyu Permatasari (Interna Publishing, 2022)
Autoimmune diseases are known to be a risk factor for severe COVID-19 infection. This is the first case series of patients with autoimmune disease suffering from COVID-19 infection in Jakarta, Indonesia. There were 12 confirmed cases of COVID-19 infection in autoimmune patients from March 2020 until February 2021. We select 5 patients in this case series. Three of them had systemic lupus erythematous (SLE), one of them had rheumatoid arthritis, and one of them had ankylosing spondylitis. Three of them had high BSR Risk Stratification. Most of them had used daily steroid therapy. Fatigue, abdominal pain, diarrhea, and cough were the common symptoms found.  None of the patients were admitted to ICU, used mechanical ventilators, and all of them survived. Most of the patients were prescribed anti-coagulant therapy. This first comprehensive case series can provide valuable information regarding the clinical characteristics of COVID-19 infection in the Indonesian autoimmune disorder patient population.